2022
DOI: 10.3390/jcm11164848
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Prediction Accuracy of Recently Updated Intraocular Lens Power Formulas with Artificial Intelligence for High Myopia

Abstract: The aim of this study was to investigate the prediction accuracy of intraocular lens (IOL) power formulas with artificial intelligence (AI) for high myopia. Cases of highly myopic patients (axial length [AL], >26.0 mm) undergoing uncomplicated cataract surgery with at least 1-month follow-up were included. Prediction errors, absolute errors, and percentages of eyes with prediction errors within ±0.25, ±0.50, and ±1.00 diopters (D) were compared using five formulas: Hill-RBF3.0, Kane, Barrett Universal II (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…Many previous studies have demonstrated that newgeneration IOL formulas such as the BU II, EVO 2.0, Kane, and RBF 3.0 formulas were more accurate in long eyes than were the traditional formulas, and two recent studies showed that the Hoffer QST formula was comparable in accuracy with the four abovementioned newer formulas. [4][5][6]8,9,22,23 Our results are consistent with those findings. However, few reports have focused on the accuracy of the K6 formula and formulas developed based on machine learning (Pearl-DGS and Nallasamy) when applied to long eyes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Many previous studies have demonstrated that newgeneration IOL formulas such as the BU II, EVO 2.0, Kane, and RBF 3.0 formulas were more accurate in long eyes than were the traditional formulas, and two recent studies showed that the Hoffer QST formula was comparable in accuracy with the four abovementioned newer formulas. [4][5][6]8,9,22,23 Our results are consistent with those findings. However, few reports have focused on the accuracy of the K6 formula and formulas developed based on machine learning (Pearl-DGS and Nallasamy) when applied to long eyes.…”
Section: Discussionsupporting
confidence: 92%
“…1,2 Updates to optical biometry have greatly improved the measurement accuracy of ocular biological parameters, but for eyes with high myopia, accurate intraocular lens (IOL) formula calculations are still challenging and controversial. [3][4][5][6] Many previous studies had focused on axial length (AL) subgroups and found that hyperopic shift occurs in traditional and some new-generation IOL formulas when AL is >26 mm. 4,[7][8][9][10] Additional ocular factors, such as corneal curvature, anterior chamber depth (measured from the epithelium to the lens), and lens thickness, may also account for the commonly observed bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…East Asia alone comprises more than half of the world's myopic population [2], with a growing trend [1][2][3][4]. In addition, the myopic tendencies observed in the present study were found to be not only restricted to ALs > 26 mm, on which this study focused, but also appeared in the medium-long AL range with lower magnitude (see Supplementary Fig.…”
Section: Discussionsupporting
confidence: 55%
“…At present, the emergence of arti cial intelligence (AI) calculation formulas based on big data has led to the development of all kinds of formulas, including the Kane, Emmetropia Verifying Optical 2.0 (EVO) and Pearl-DGS formulas [15][16][17] . The most important feature of this type of formula is its self-learning ability, and it is expected to make a breakthrough in the eld of accurate computing after refractive surgery.…”
Section: Introductionmentioning
confidence: 99%